Physical exercise keeps the brain connected by increasing white matter integrity in healthy controls. Issue 35 (3rd September 2021) - Bashir, Shahid; Al-Sultan, Fahad; Jamea, Abdullah Abu; Almousa, Abdullah; Alnafisah, Mohammed; Alzahrani, Maha; Abualait, Turki; Yoo, Woo-Kyoung
Abstract : Abstract: Physical exercise leads to structural changes in the brain. However, it is unclear whether the initiation or continuous practice of physical exercise causes this effect and whether brain connectivity benefits from exercise. We examined the effect of 6 months of exercise on the brain in participants who exercise regularly (n = 25) and in matched healthy controls (n = 20). Diffusion tensor imaging brain scans were obtained from both groups. Our findings demonstrate that regular physical exercise significantly increases the integrity of white matter fiber tracts, especially those related to frontal function. This implies that exercise improves brain connectivity in healthy individuals, which has important implications for understanding the effect of fitness programs on the brains of healthy subjects.